A review of stability and progress in tin halide perovskite solar cell - Aftab A.; Ahmad M.I. (My University, 2025)
A systematic understanding of degradation mechanism and parameters affecting the stability of tin-based perovskite solar cell (PSC) is essential to pave the way for its commercialization and large scale implementation. Sn-based PSCs are susceptible to degradation in ambient air, moisture, water, high temperature and UV lights, which affect the overall performance of the cell. The major reason for poor stability and performance of tin-based perovskites includes the rapid oxidation of Sn2+ into its most stable Sn4+ state, uncontrolled crystallization of Sn-perovskite and mismatch of band alignment of Sn-perovskite with either electron transport layer (ETL) or hole transport layer (HTL). Other factors which adversely affect the stability and performance of PSCs include ion migration, charge recombination and hysteresis. The viable pathways to facilitate the improvement in performance and stability of Sn-based perovskite absorber layer include solvent engineering (addition of additives and dripping of anti-solvent), incorporation of larger cations, mixing of anions; however, the overall device performance can be improved by changing device structure, proper selection of HTL and ETL materials and encapsulation. This review takes an opportunity to shed light on the factors and mechanism which lowers the stability and performance of the cell. Some of the possible approaches to boost its efficiency and stability are also highlighted in this review article. © 2021 International Solar Energy Society